ANALISIS BATASAN PEREDARAN BRUTO USAHA ATAS PELAKSANAAN PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 - R. Soerjatno (Politeknik Ubaya, 2017)
The policy on the enactment of Government Regulation No. 46 of 2013 is based on the consideration to facilitate taxpayers in calculating the tax so that more taxpayers are expected to register as taxpayers because of the ease in calculating the tax.Government Regulation No. 46 of 2013 is applied to Taxpayers having gross turnover up to Rp.4.800.000.000,00 a year and not applicable to those who have income from free employment (doctors, notaries etc.). PP46 tariff is 1% of Gross business turnover so that any Brule Distribution will be subject to Income Tax of 1% of Gross Distribution. However, in Law No.7 of 1983 as amended by Act no.36 of 2008 in Article 17 paragraph (1) in the explanation states that Tax Payable Individual Taxpayer is Tariff Psl.17 Income Tax Law multiplied by Income Taxable Tax, while based on Article 16 paragraph (2) of Income Tax Law, Taxable Income for WP Person is Net Income minus Non Taxable Income. Based on the calculation difference, the authors conducted the study in order that the implementation of tax rules remains procedural and easy but still has a sense of justice especially for small Taxpayers .